Culturally Responsive Teaching (CRT) Approach in Social Science and Science Learning Elementary School: A Bibliometric Study from 2020-2025 - Isna Rachma Nirmala; Murbangun Nuswowati; Bambang Subali; Ellianawati (JIP Jurnal Ilmiah PGMI, 2025)
Culturally Responsive Teaching (CRT) approach is very important to adopt because it is able to integrate cultural values and experiences of students into learning, thus creating an inclusive, relevant, and adaptive learning environment to the needs of students. This study aims to explore the application of the Culturally Responsive Teaching approach in learning Natural and Social Sciences (IPAS) in Elementary Schools. The research method chosen is a systematic literature review by analyzing 1,011 articles from the Scopus and Google Scholar databases published in the 2020-2025 period. The results of the analysis of various articles, the application of the Culturally Responsive Teaching approach in IPAS learning can increase motivation, participation, 21st century skills, and learning outcomes of students, especially in the context of cultural diversity in the classroom. The research gap that can be filled based on the results of the analysis is the application of the Culturally Responsive Teaching approach in IPAS learning not only on the learning outcomes of cognitive aspects but also affective aspects and 21st century skills as a whole . In addition, the Culturally Responsive Teaching approach encourages teachers to be more innovative in designing learning strategies that are adaptive to the needs and characteristics of students. Thus, Culturally Responsive Teaching can be a strategic solution in developing science learning that is in line with the demands of 21st century education in Elementary School.